Ritual Mandi Safar: Akulturasi Islam dan Tradisi Lokal: Studi Kasus di Desa Air Hitam Laut Kecamatan Sadu Kabupaten Tanjung Jabung Timur - L, Bahtiar; Mursalin, Ayub; Masburiah, Masburiah (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
This research aims to show up the local islamic society tradition named Ritual Mandi Safor which getfocusfrom various community of islam itself. Riual Mandi Safar represents one of local area ancestor heritage assumed can refuse misfortunes (accident, disaster and disease epidemic). However as the local tradition which is related to islam, it generate pros and contra among the society that support and also refuse it. Relating to that reason, this research aims tofind the meaning of symbol and function of Ritual Mandi Safar for the society that support it. How far their understanding to this rittral and the advantages for their daily life and also the role of local government to remain this tradition.